ANALISIS PEMASARAN JERUK SIAM GUNUNG OMEH (Citrus nobilis lourvar) DI NAGARI KOTO TINGGI KECAMATAN GUNUNG OMEH KABUPATEN LIMA PULUH KOTA - Sri Ella Gisti; Suardi Tarumun; Jum'atri Yusri (Fakultas Pertanian, Universitas Riau, 2018)
This research was aimed to determine the marketing function, marketing channels, margin, profit, efficiency and institution problems of Siamese citrus. The data used in this research was primary and secondary data. This research applied survey method and random sampling method for selecting farmer respondents. Snowball sampling was used for selecting marketing institution through the marketing channels. There are two marketing channels, the first channel is farmers-collecting merchants-retailers-consumers. The second channel is farmers-retailers-consumers. The research result showed that the efficient marketing channels for the first channel is grade A, and for the second channel is grade B. The highest total profit for the first channel is grade C and for the second channel is grade B. Margin on first channels are grade B and C and on the second channel the margin is on grade B. The farmer share of the first channel is on grade A and of the second channel is on grade A. Several institution problems are price fluctuation, pests and breakdown products.